Examining teaching orientation challenging subject in the 21st century regarding cell biology - Thilaworrakan, Nunnapat; Ladachart, Ladapa (Technium Social Sciences Journal, 2021)
Advances in science and technology the educational paradigm has been transformed into constructivism, a changing context, so the nation's people's resources must be prepared as soon as possible. Therefore, education must focus on people thinking about being and solving problems, the teaching needs to be adapted from passive learning to active learning, focusing on students being able to analyze and seek their knowledge. Teachers as an educational profession need to be aware of their teaching methods. This research report aims to study the teaching beliefs of biology teachers on specific topics as part of pedagogical content knowledge (PCK) is considered necessary for teaching science teachers. The researchers collected data from a sample of 10 biology teachers using a measure of faith in biology, improved from Cobern et al. (2014). According to the research, teachers believe in teaching between active direct and guided inquiry, but when conducting an interview, the majority of teachers use didactic teaching models. This research reflects the reality of teacher teaching and the challenges that go through the country's educational crisis into the 21st century.